Criminalization of Cartels in India & its Legal Implications: Exploring the Consequences of Cartel Activities in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Competition Act of 2002 prohibits cartel activity in India. Section 3(1) of the demonstrationprohibits cartel planning and should be interpreted in conjunction with Section 3(3). The Cartelarrangement is considered illegal as it seeks to manipulate market conditions and establish prices, thusviolating the Competition Act of 2002. A cartel is an organisation of manufacturers, retailers,wholesalers, retailers, traders, or service providers that, via agreements among themselves, restrict,control, or attempt to regulate the production, distribution, sale, price, or trade of goods or services.Cartels may also be referred to as monopolies. This concept originates from the Act ConcerningCompetition. Cement manufacturers have been accused of participating in price manipulation by bothprivate persons and government agencies for more than a decade now. In 2016, the CompetitionCommision of India (CCI) imposed penalties amounting to 800 million on ten companies, includingvarious subsidiaries of Holcim and UltraTech, for their involvement in price fixing. However, this ruling iscurrently under scrutiny and is being contested in the Supreme Court. The objective of this study is toexamine the legal ramifications of cartels in India.